INTERFERENSI BAHASA LAMAHOLOT DIALEK LEWOAWAN TERHADAP PENGGUNAAN BAHASA INDONESIA PADA MASYARAKAT DESA LEWOAWANG - Leba, Bartoldus Sora ((JIBS) JURNAL ILMIAH BAHASA DAN SASTRA, 2023)
This study aims to explain the interference of Lewoawan dialect Lamaholot language (SL) on the use of Indonesian (TL) by the people of Lewoawan Village. This study uses qualitative descriptive approach. Data collection was carried out using the technique of free-involved viewing, speaking, and note-taking. The researcher is the key instrument who is supported by some supporting instruments. The data collected is the utterances of Lewoawang dialect Lamaholot language. The data analysis technique used is data reduction, data presentation, and drawing conclusions The findings in this study could be presented as follows several types of interference namely phonological interference, syntactical interference and lexical interference. Phonological interference includes changing the pronunciation of the phoneme [Ç] to [É›] and monophthongization. Syntactic interference occurs because Indonesian is spoken using the Lewoawan dialect of the Lamaholot language interrogative structure and also the use of affirming particles. Those particles that are often used in speaking are the particles ka, to, ni and tu. The particle â€˜kaâ€™ is used to express the meaning of affirmation in interrogative sentences, the particle to is used to express indifference to what is conveyed, while the particles ni and tu express affirmation in demonstrative sentences that refer to place. Meanwhile, lexical interference includes the use of words.